Clinical Probability Assessment using Modified Wells Criteria and D-Dimer for Diagnosis of Lower Limb DVT - Shah, Santosh; Poudel, Rajesh; Miya, Sabir (Medical Journal of Eastern Nepal, 2024)
Background Deep vein thrombosis (DVT) is a frequent problem in ambulatory and hospitalized patients. It is linked to considerable illness and death related to post-thrombotic syndrome, pulmonary embolism (PE), and pulmonary hypertension secondary to chronic PE. The comparitively low prevalence of DVT leads to a significant number of negative initial ultrasound (US) examinations. A combination of clinical pretest probability assessment using Modified Wells Score (MWS) and D-Dimer testing and subsequent venous US is a good diagnostic approach. Methods This study is a drescriptive cross-sectional analysis on patients attending UCMS hospital with suspected DVT from September 2021 to March 2023 in order to evaluate the reliability of a combined approach of clinical assessment score (Modified Wells Score) followed by D-dimer test to exclude deep vein thrombosis. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of Modified Wells Score and D-Dimer individually and in combination were noted as outcomes. Results The study was undertaken in 79 patients. Among the patients, 31 out of 79 (39.24%) were confirmed to have DVT (group one), while 48 patients (60.76%) were ruled out for DVT (group two). In individual Modified Wells Score both the sensitivity and PPV were found to be 77.4%, and both the specificity and NPV were found to be 85.4%. The individual D-dimer test sensitivity was 93.5% with a specificity of 87.5%, while PPV and NPV were 82.9% and 95.5%, respectively. In combined strategy the sensitivity, specificity, PPV and NPV for the likely group combined with D-dimer test results were 100%, 42.9%, 85.7% and 100% respectively. The sensitivity, specificity, PPV and NPV for unlikely group combined with D-dimer test results were 71.4%, 95.1%, 71.4% and 95.1% respectively. Conclusion Combination of Modified Well’s Criteria along with D-dimer level increases the sensitivity and Negative Predictive Value in DVT diagnosis in suspected cases.